Analisis Penentuan Sektor Unggulan Perekonomian Wilayah Kabupaten Dairi - Tamaria Sidebang; Deyren Firmansyah; Mentari Rezeki Ramadhani (Universitas Battuta, 2025)
This research aims to determine the leading sectors of the regional economy in Dairi Regency. This research uses secondary data in the form of a time series of Gross Regional Domestic Product (GRDP) Dairi Regency and North Sumatra Province 2019-2023. Analytical tools used in This research is 1.) Location Quantient (LQ) analysis, this analytical tool is used to determine sectors base and non-base on the economy in the Dairi Regency area. 2.) This Shift Share analysis is used for understand changes and shifts in the economic structure in the Dairi Regency area. From the results of the analysis has been used through two analytical tools which have shown the leading sectors in the Dairi Regency area with the criteria for being classified as a basic and competitive sector, namely the agricultural sector, accommodation provision, government administration, and educational services.